Effect of Elevated Ketone Body on Maternal and Infant Outcome of Pregnant Women with Abnormal Glucose Metabolism During Pregnancy - Qian, Meichen (Diabetes Metab Syndr Obes, 2020)
Ketone bodies are one of the products of fat metabolism which can be used as an alternative energy source for the human body in states of glucose deficiency. Normal pregnant women may develop ketosis due to physiological changes during pregnancy, while pregnant women with abnormal glucose metabolism are more likely to develop ketosis due to abnormal insulin secretion. Animal experiments and clinical studies have shown that exposure to high-ketone environments during pregnancy is closely related to adverse maternal and infant outcomes. However, there is no unified conclusion on whether ketone bodies should be routinely monitored during pregnancy. This review summarizes the existing studies on ketone body levels and pregnancy outcomes in the case of abnormal blood glucose during pregnancy, elaborates the current guidelines on the level of ketone bodies, provides the detection and treatment of ketosis in pregnant women with abnormal blood glucose in the clinical practice.